The Relationship Between Peer Social Support and Self-Adjustment of Overseas Students from South Sumatra in Yogyakarta - Sari, Afni Ambar; Syariful, Syariful (Sean Institute, 2025)
Migrant students often encounter substantial challenges when adapting to new academic and social environments, including cultural differences, language barriers, and unfamiliar social norms. These obstacles may hinder their psychological and social adjustment, making peer social support an essential factor in facilitating their adaptation. This study aims to examine the relationship between peer social support and self-adjustment among migrant students from South Sumatra studying in Yogyakarta.Using a quantitative correlational method, the study involved 105 South Sumatran students enrolled in various higher education institutions in the Special Region of Yogyakarta. Participants were selected through purposive sampling, with the criteria of being active students who had studied for at least one year. Data were collected using a peer social support scale based on House’s theory (1981) and a self-adjustment scale based on Schneider’s theory (1999). Validity testing resulted in the exclusion of one item from the peer support scale and three items from the self-adjustment scale. Reliability testing using Cronbach’s Alpha produced coefficients of 0.917 for peer social support and 0.938 for self-adjustment.Correlation analysis revealed a positive and significant relationship between peer social support and self-adjustment, with a correlation coefficient of 0.822 and a significance value of 0.000 (p < 0.05). These findings indicate that higher levels of peer social support are associated with better self-adjustment among migrant students. The study highlights the crucial role of peer relationships in supporting migrant students’ psychological well-being and academic adaptation in a new environment.